Efficacy and safety of non‐pharmacological interventions for endotracheal suctioning pain in preterm infants: A systematic review - Qian Cai; Wen Luo; You Zhou; Yue Yin; Kai Zhu; Huan Shi; Yuexia Liao (Wiley, 2023)
Abstract Aim To review and analyse the evidence on the efficacy and safety of non‐pharmacological interventions for preterm infants to relieve endotracheal suctioning (ES) pain. Design A systematic review per the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Methods Six databases were searched with a retrieval strategy. Parallel and crossover randomized controlled trials reporting non‐pharmacological interventions for relieving ES pain in preterm infants were identified from inception to 1 September 2021. The protocol was published in PROSPERO (CRD42021276058). Results Ten studies were retrieved, including nine different non‐pharmacological interventions. Seven studies reported that non‐pharmacological interventions in relieving pain were more effective than conventional care during ES, and three trials reported its safety. Due to the heterogeneity of pain assessment tools, time of assessment and population, only Facilitated tucking had sufficient evidence that it is a safe and effective non‐pharmacological intervention.